Anatomia Ecológica foliar de Orchidaceae de Mata Atlântica de Interior (Parque nacional do Iguaçu), Paraná, Brasil - Moreira, Débora Marcília (2022)
Very well represented among Angiosperms and, specifically in the Brazilian Atlantic Forest, Orchidaceae has wide ecological diversity, including the substrate of occurrence. Its members are identified mainly because they are made up of zygomorphic flowers gathered in inflorescences, alternate leaves, with simple and parallel venation. The pseudobulb and velamen may occur, which, when present, are also relevant structures for characterization. Orchids dominate various types of substrates, but the most representative is epiphytic. Epiphytism is often one of the aspects that lead to morphological and anatomical particularities capable of facilitating the survival of species in more restrictive locations. The family has representatives already registered for the Iguaçu National Park (ParNa Iguaçu), a conservation area, an important remnant of the interior Atlantic Forest, with a high richness of Orchidaceae species. Thus, in this study, morphological characteristics and leaf anatomy of 38 species of Orchidaceae belonging to ParNa Iguaçu were analyzed, also providing statistical data that served as a basis for creating functional groups among the species of the family included in this study. For leaf anatomical analyses, freehand transverse sections were stained with Alcian Blue and Basic Fuchsin. Histochemical tests were carried out with Ferric Chloride, Sudam IV, Lugol, Methylene Blue and Phloroglucinol. Statistics made it possible to group the species, based on similar characters between them, into three distinct functional groups. The first was made up of species with xeromorphic characteristics, the second was made up of orchids with mesomorphic to hygromorphic characters and the third was made up of just one species. The 10 analyses of all morphological and anatomical leaf characteristics, species by species, made it possible to develop the ecological anatomy for these orchids from ParNa Iguaçu. Most of species had phenolic compounds, starch and mucilage in the mesophyll and epidermis. Although the presence of lignin was not found in tracheoidal idioblasts, several plants had lignified cells in the vascular bundles and fiber strands. Many morpho-anatomical characteristics appear to be inherent representatives of members of the family or genus. Most of the characteristics are related to water availability, exposure to sunlight, winds and defense against herbivores and pathogens. This suggests that plants can survive in different environments, with some being more resistant to such factors and others being more vulnerable, with few survival strategies to sudden environmental changes. The results show the necessary modeling of practices aimed at conserving these species, initially considering their differences in habitat preference. The work provides an increase in the functional knowledge of plants, which can contribute to appropriate management work for the species. May this study inspire further research associated with the ecological anatomy of the park's flora in order to provide support for botanical management and conservation.